Technology Gap, Reverse Technology Spillover and Domestic Innovation Performance in Outward Foreign Direct Investment: Evidence from China - Hong, J.; Zhou, C.; Wang, R.; Wu, Y.; Marinova, Dora (WILEY, 2019)
This research adds to the literature studying the effects of outward foreign direct investment (OFDI) on domestic innovation performance and the moderating effect of a technology gap between host and home countries. New definitions of observed technology gap and expected technology gap are proposed. An observed technology gap captures the existing differences in technology level between establishments, regions or countries. An expected technology gap is an indication of the effort of imitating and learning from technology leaders. The corresponding measures and effects of observed and expected technology gaps on OFDI-induced reverse technology spillover are analyzed. OFDI in developed countries promotes innovation performance. However, OFDI in emerging markets hampers innovation performance. It is also found that regions with a wider observed technology gap and a narrower expected technology gap can benefit more from OFDI.